2020
DOI: 10.2169/internalmedicine.3358-19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Rapidly Progressive Fatal Hemorrhagic Pneumonia Caused by <i>Stenotrophomonas maltophilia</i>

Abstract: Objective Hemorrhagic pneumonia due to Stenotrophomonas maltophilia (SM) in severely immunocompromised patients has a very poor prognosis. However, the risk factors for hemorrhagic pneumonia are not clear. Methods This study assessed the predictive factors of hemorrhagic pneumonia caused by SM. The medical records of patients admitted to Osaka City University Hospital with SM bacteremia between January 2008 and December 2017 were retrospectively reviewed. Patients All patients who had positive blood cultures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…In the present study, the overall mortality rate of SM bacteremia in patients with hematologic diseases was 67.3%, which was comparable to that obtained in past studies, ranging from 35-75% [8][9][10][11][12]. The mortality rate of SM bacteremia with hemorrhagic pneumonia was signi cantly higher than those without hemorrhagic pneumonia.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the overall mortality rate of SM bacteremia in patients with hematologic diseases was 67.3%, which was comparable to that obtained in past studies, ranging from 35-75% [8][9][10][11][12]. The mortality rate of SM bacteremia with hemorrhagic pneumonia was signi cantly higher than those without hemorrhagic pneumonia.…”
Section: Discussionsupporting
confidence: 86%
“…Due to the intrinsic resistance of SM to many broad-spectrum antimicrobial agents, it is di cult to determine the appropriate antibiotic treatment before the SM is detected [2,7]. Therefore, previous studies have shown a very poor prognosis in the cases of SM bacteremia, and the overall mortality was ranged from 35 to 75% [8][9][10][11][12]. Noteworthy, in patients with hematologic malignancies and/or hematopoietic stem cell transplantation (HSCT) recipients, SM can cause fatal hemorrhagic pneumonia, and the mortality is nearly 100% [10,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulmonary haemorrhage caused by Stenotrophomonas maltophilia is a rare condition with a poor outcome. Several reports have shown the presence of predisposing factors like severe thrombocytopenia, severe and prolonged neutropenia, the previous use of quinolones, corticosteroids, and immunosuppressive therapy [2,8,9]. Our patient had grade IV thrombocytopenia and neutropenia secondary to chemotherapy.…”
Section: Discussionmentioning
confidence: 60%
“…In the published literature, we found 34 haematological patients with Stenotrophomonas maltophilia and pulmonary haemorrhage [2,8]. Most patients (22 out of 34) were diagnosed with acute myeloid leukaemia, and the mortality rate was 100%, and the survival length was 0-43 days.…”
Section: Discussionmentioning
confidence: 99%